Determination of five alcohol compounds in fermented Korean foods via simple liquid extraction with dimethyl-sulfoxide followed by gas chromatography-mass spectrometry for Halal food certification. (December 2016) - Park, Sunhyun; Kim, Jong-Chan; Lee, Hyun Sung; Jeong, Seung-Weon; Shim, You-Shin
Abstract: An analytical method for the determination of five alcohols (methanol, ethanol, n-propanol, n-butanol and n-pentanol) in fermented Korean foods using gas chromatography-mass spectrometry (GC/MS) was validated in terms of precision, accuracy, sensitivity and linearity. GC/MS separation was performed on a silica-based INNOWAX column (film thickness 0.25 μm, i.d. 250 μm, length 30 m) coated with polyethylene glycol and a mass selective detector set to determine specific selected ions for each alcohol. The limits of detection and quantification of the GC/MS analyses ranged from 0.25 to 1.16 mg/kg. Intra-day and inter-day RSDs for individual alcohol compounds were below 7%, and calibration curves exhibited good linearity ( r = 0.999) within the tested ranges. Recovery values ranged from 90.79 to 101.50%. These results suggest that the analytical method described in this study could be used to determine the concentrations of five alcohols in a variety of fermented Korean foods such as Gochujang, Kimchi and soybean sauce (paste, solid and liquid sample) for Halal food certification. Highlights: Establishment of rapid and simple pretreatment method for 5 alcohol compounds. Establishment of detection method for 5 alcohols using GC/MSD. Established method was validated through precision, accuracy and linearity. Application test for Korean fermented foods such as Gochujang and soybean sauce.